Integrasi Nilai Ajaran Islam dalam Tradisi Nunas Neda: Studi Kasus di Desa Kesik, Lombok Timur - Dinnia Nova Ayu Rizkika; Jumarim Jumarim; Lalu Muhammad Nurul Wathoni (LEMBAGA PENELITIAN DAN PENDIDIKAN (LPP) ARROSYIDIN, 2026)
This study aims to identify the values ??of Islamic Religious Education contained in the Nunas Neda tradition. This study uses a qualitative approach with an ethnographic approach. Data collection techniques were conducted through observation, semi-structured interviews, and documentation. The research data sources consisted of religious leaders, traditional leaders, ritual practitioners, and the Kesik Village community. Data analysis was conducted through data reduction, data presentation, and conclusion drawing. The results show that: (1) the Nunas Neda tradition procession consists of a preparatory stage (ngayu-ayu), core activities such as prayer, remembrance of God (zikir), a harvest procession, a ritual at a spring, and a closing event consisting of a communal meal as an expression of gratitude; (2) the values ??of Islamic Religious Education contained include faith, worship, and morals; and (3) the integration of Islamic values ??includes integration through diffusion, acculturation, assimilation, and inculturation. The Nunas Neda tradition serves not only as a local cultural heritage but also as a medium for internalizing Islamic values ??that strengthen spirituality, social solidarity, and community harmony.